Codeswitching in communication: a sociolinguistic study of Malaysian secondary school students - Muthusamy, Paramasivam (Universiti Putra Malaysia Press, 2010)
Codeswitching is a common phenomenon in a multilingual society like Malaysia. Furthermore, the language policy of the Malaysian government has made it mandatory for the students to learn both in bahasa melayu and English at their primary school level. The Indian and Chinese students acquired their respective mother tongues, namely Tamil and Mandarin, besides the two compulsory languages, (bahasa Melayu and English). This study was conducted at four secondary schools situated in the Klang Valley, in which one school was chosen from an urban setting, two from suburban, and one from a rural area. Twenty samples were selected of which twelve were Indian students, four Malays, and four Chinese. The samples were give two topics for discussion and their conversations were recorded and transcribed. In addition, a questionnaire was administered to determine the respondents' demographic details and their language choice at home. The findings indicated that codeswitching that occurs from bahasa Melayu to English, Tamil or Chinese to English or vice versa during conversations is more habitual by nature. Respondents from the average economic and educational category were found to have used both English and their mother tongue as their matrix language. However, the respondents from the lower economic and educational category used their mother tongue as the dominant language or matrix language. Similarly, when the same ethnic group converse, their mother tongue becomes the domain language, with English and bahasa Melayu as the embedded languages.